EDUKASI PENINGKATAN GIZI ANAK DALAM UPAYA CEGAH STUNTING DI GUNUNG GEULIS - Hari Susanto, Lufty; Lathifah, Suci; Ardianto, Didit; Naziela Zaura Irawan, Nazwa; Siti Nurjanah, Alifia; Ranuma Dely, Indriani (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
The community service program on child nutrition education aimed at preventing stunting in Desa Gunung Geulis sought to address the high prevalence of stunting due to nutritional issues. Initial situation analysis revealed that 40% of children in the village experienced stunting, with 70% of parents having limited knowledge about balanced nutrition. Based on these findings, comprehensive and easily understandable educational materials and training modules were developed, covering essential information on balanced nutrition, types of nutritious foods, and methods for preparing and presenting healthy meals using local ingredients. The outreach and training were conducted at three strategic locations and attended by 150 parents and caregivers, employing interactive and practical methods. Follow-up support and monitoring over three months showed that 80% of the families improved their children’s nutritional intake. The final evaluation indicated a significant increase in parental knowledge about nutrition from 30% to 85% and a reduction in stunting prevalence from 10% to 8% within six months. These results demonstrate that a structured, community-based educational approach effectively enhances nutritional knowledge and reduces stunting, significantly impacting child well-being in Desa Gunung Geulis.